The perspectives of older drivers on the impact of feedback on their driving behaviours: A qualitative study. (January 2015) - Hassan, Heidy; King, Mark; Watt, Kerrianne
Highlights: Focus group sessions were conducted with older drivers. We explored older drivers' perceptions and experiences of self-regulation. The Precaution Adoption Process Model was used as a framework. We investigated the possible impact of feedback on their decision making process. Relevant issues that should be further investigated are discussed. Abstract: Self-regulation is a coping strategy that allows older drivers to drive safely for longer. Self-regulation depends largely on the ability of drivers to evaluate their own driving. Therefore the success of self-regulation, in terms of driving safety, is influenced by the ability of older drivers to have insight into their declining driving performance. In addition, previous studies suggest that providing feedback to older adults regarding their driving skills may lead them to change their driving behaviour. However, little is currently known about the impact of feedback on older drivers' self-awareness and their subsequent driving regulatory behaviour. This study explored the process of self-regulation and driving cessation among older drivers using the PAPM as a framework. It also investigated older adults' perceptions and opinions about receiving feedback in regards to their driving abilities. Qualitative focus groups with 27 participants aged 70 years or more were conducted. Thematic analysis resulted in the development of five main themes; the meaning of driving, changes in driving pattern, feedback, the planning process, and solutions. The analysis also resulted in an initial model of driving self-regulation among older drivers that is informed by the current research and the Precaution Adoption Process Model as the theoretical framework. It identifies a number of social, personal, and environmental factors that can either facilitate or hinder people's transition between stages of change. The findings from this study suggest that further elaboration of the PAPM is needed to take into account the role of insight and feedback on the process of self-regulation among older drivers.